Early Barriers to Neonatal Porcine Islet Engraftment in a Dual Transplant Model - Samy, KP (Am J Transplant, 2017)
Porcine islet xenografts have the potential to provide an inexhaustible source of islets for β cell replacement. Proof-of-concept has been established in nonhuman primates. However, significant barriers to xenoislet transplantation remain, including, the poorly understood instant blood mediated inflammatory reaction (IBMIR), and a thorough understanding of early xeno-specific immune responses. A paucity of data exist comparing xeno-specific immune responses to allo-islet responses in primates. We recently developed a dual islet transplant model, which enables direct histological comparison of early engraftment immunobiology. In this study, we investigate early immune responses to neonatal porcine islet (NPI) xenografts compared to rhesus islet allografts at 1 hour, 24 hours, and 7 days. Within the first 24 hours after intraportal infusion, we identified greater apoptosis (caspase 3 activity and TUNEL positive cells) of NPIs when compared to alloislets (AIs). Macrophage infiltration was significantly greater at 24 hours compared with 1 hour in both NPI (WT) and AIs. At 7 days, IgM and macrophages were highly specific for NPIs (GTKO) compared to AIs. These findings demonstrate an augmented macrophage and antibody response towards xenografts compared to allografts. These data may inform future immune or genetic manipulations required to improve xenoislet engraftment.